Esprit universitaire ou esprit étudiant. La recherche d'identité des étudiants de l'Université McGill et de l'Université de Montréal (1900-1960) - Hébert, Karine (Les transformations des universités du XIIIe au XXIe siècle, 2006)
Keywords: Université McGill; Université de Montréal; Étudiants

Carabines, poutchinettes co-eds ou freschettes sont-elles des étudiantes? Les filles à l’Université McGill et à l’Université de Montréal (1900-1960) - Hébert, Karine (Revue d'histoire de l'Amérique française, 2004)
Keywords: Femmes; Université McGill; Université de Montréal; Étudiants

Parts in Play: The Rosalynde Osborne Stearn Collection at McGill University - Flegel, Loretta (Université Concordia, 2003)
Keywords: Théâtre; Université McGill

A Scout of the Past: Ramsay Traquair and the Legacy of the National Art Survey of Scotland in Quebec - Murray, Irena (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Université McGill; Écossais

McGill Medicine. Vol. 2 - 1885-1936 - Hanaway, Joseph; Cruess, Richard L.; Darragh, James (McGill-Queen's University Press, 2006)
Keywords: Médecine; Université McGill

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

L’Office provincial des recherches scientifiques et le développement de la science au Québec, 1937-1960 - Almeida, Mike (Revue d'histoire de l'Amérique française, 2002)
Keywords: Université McGill; Université de Montréal

Les transformations des universités du XIIIe au XXIe siècle - Gingras, Yves; Roy, Lyse (Presses de l'Université du Québec, 2006)
Keywords: Université McGill; Université de Montréal

Student Life at McGill: 1936-1940 - Lévesque, Andrée (Madeleine Parent: Activist, 2005)
Keywords: Parent, Madeleine; Université McGill

Impatient d’être soi-même. Les étudiants montréalais, 1895-1960 - Hébert, Karine (Presses de l'Université du Québec, 2008)
Keywords: Université McGill; Université de Montréal; Étudiants

From Tomorrow’s Elite to Young Intellectual Workers: The Search for Identity among Montreal Students, 1900-1958 - Hébert, Karine (Negotiating Identities in 19th and 20th Century Montreal, 2005)
Keywords: Université McGill; Université de Montréal; Étudiants

Between the Future and the Present: Montreal University Student Youth and the Post-War Years, 1945-1960 - Hébert, Karine (Cultures of Citizenship in Post-War Canada, 1940-1955, 2003)
Keywords: Université McGill; Université de Montréal; Étudiants

La construction d'une identité étudiante montréalaise (1895-1960) - Hébert, Karine (Université du Québec à Montréal, 2002)
Keywords: Université McGill; Université de Montréal; Étudiants

The Early History of Medical Genetics in Canada - Leeming, William (Social History of Medecine, 2004)
Keywords: Médecine; Université McGill; Université de Montréal

Club Life / La Vie au Club - Robertson, Louise (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

Club Personalities / Les Personnalités du Club - MacKell, Peter R. D. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

The Club Building / L'Édifice du Club - Drummond, Derek A. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007 - MacKell, Peter R. D. (Price-Patterson Ltd, 2007)
Keywords: Clubs; University Club; Université McGill

The Beginning – The University Club in the Life of Montreal / Les débuts: Le Club universitaire au coeur de la vie Montréalaise - MacKell, Peter R. D. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

From Osler’s Library to the Osler Library of the History of Medicine, McGill University, Montreal: An Overview - Lyons, Christopher (Canadian Bulletin of Medical History, 2007)
Keywords: Bibliothèque Osler; Médecine; Université McGill

Anatomically Incorrect: Bodysnatching in the Nineteenth Century - Rankin, Matthew (The Beaver, 2002)
Keywords: Criminalité; Médecine; Université McGill; Étudiants

Un projet d’enquête sur la jeunesse universitaire (1913) - Trépanier, Charles (Les Cahiers des Dix, 2000)
Keywords: Groulx, Lionel; Université McGill; Université de Laval à Montréal

The Club Art Collection / La Collection d'oeuvres d'art du Club - Murphy, Sean B. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Peinture; University Club; Université McGill

Club Staff Over the Years / Le Personnel du Club au cours des années - MacKell, Peter R. D.; Armstrong, Julian (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Travail; University Club; Université McGill

Opération McGill français - Warren, Jean-Philippe (Une douce anarchie. Les années 68 au Québec, 2008)
Keywords: Anglophones; Associations étudiantes; Francophones; Université McGill

Les étapes de la science économique au Québec: démarrage, construction et maturité - Fortin, Pierre (L'Actualité économique, 2000)
Keywords: Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal

Les ingénieurs sanitaires à Montréal, 1870-1945: lieux de formation et exercice de la profession - Gagnon, Robert; Zwarich, Natasha (Urban History Review / Revue d'histoire urbaine, 2008)
Keywords: Fonctionnaires; Ingénieurs; Université McGill; Université de Montréal; École polytechnique

Infrastructures urbaines et santé publique: l'émergence de la spécialisation du génie sanitaire à Montréal, 1892-1945 - Zwarich, Natasha (Université du Québec à Montréal, 2004)
Keywords: Fonctionnaires; Ingénieurs; Université McGill; Université de Montréal; École polytechnique

Dans le mouvement étudiant à McGill - Lévesque, Andrée (Madeleine Parent, militante, 2003)
Keywords: Mouvement étudiant; Parent, Madeleine; Université McGill; Étudiants

The Club and the Two World Wars / Le Club et les deux guerres mondiales - Claxton, John B. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Guerre; Poésie; University Club; Université McGill

Changing Times / Les temps changent - K. Paterson, Alex (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Femmes; Juifs; University Club; Université McGill

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Keywords: McEachran, Duncan McNab; Université McGill; École de médecine vétérinaire

Wine and Food / Cuisine et vins - M. Romoff, Harvey (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Alcool; Alimentation; Clubs; Restaurant; University Club; Université McGill

Sir William C. Macdonald. A Biography - Fong, William (McGill-Queen's University Press, 2007)
Keywords: Macdonald College; Macdonald, William C.; Philanthropie; Tabac; Université McGill

L'opération McGill français. Une page méconnue de l'histoire de la gauche nationaliste - Warren, Jean-Philippe (Bulletin d'histoire politique, 2008)
Keywords: Anglophones; Associations étudiantes; Francophones; Groupes populaires; Université McGill; Université de Montréal; Université du Québec à Montréal

Rocke Robertson: surgeon and shepherd of change - Pound, Richard W. (McGill-Queen's University Press, 2008)
Keywords: Anglophones; Hôpitaux; Montreal General Hospital; Médecine; Université McGill; École de médecine

J.W. McConnell: Financier, Philanthropist, Patriot - Fong, William Jesse (McGill-Queen's University Press, 2008)
Keywords: Clubs; Hommes d'affaires; McConnell, John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

Les pierres de constructions m'ont raconté: une visite guidée de fossiles, roches et minéraux d'édifices montréalais - Birker, Ingrid; Kaylor, Joan; Gillingwater, Trevor (Musée Redpath et Université McGill, 2005)
Keywords: Géologie; Paléontologie

What building stones tell. A walking tour guide focusing on the fossils, rocks, and minerals of Montreal's buildings - Birker, Ingrid; Kaylor, Joan; Gillingwater, Trevor (Musée Redpath et Université McGill, 2002)
Keywords: Géologie; Paléontologie

Shared Values, Different Paths: First-Generation Iranian Men's and Women's Perceptions of the Cultural Production of an "Educated Person" - Sadeghi, Shiva (Université McGill, 2004)
Keywords: Iraniens; Étudiants

Self-Identification Processes and their Reflection in the Language of Fourth-Wave Emigrants in Montreal - Migdissova, Svetlana (Université McGill, 2003)
Keywords: Langue; Russes

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Sankofa: Recovering Montreal’s Heterogeneous Black Print Serials - Williams, Dorothy W. (Université McGill, 2006)
Keywords: Noirs

Représentations culturelles et identité d'immigrants adultes de Montréal apprenant le français - Amireault, Valérie (Université McGill, 2007)
Keywords: Langue

Entre globalisation et réalités locales: centres commerciaux et formes urbaines à Los Angeles, Montréal et Paris / Between Globalization and Local Realities: Shopping Centers and Urban Forms in Los Angeles, Montreal and Paris - Moretti, GianPiero (Université McGill, 2004)
Keywords: Centres commerciaux

Deviance and Social Control among Haredi Adolescent Males - Levy, Jonathan (Université McGill, 2004)
Keywords: Juifs

Forging the Corporate Identity with Art: Four Montreal Corporations: Alcan Aluminium Limited, Martineau Walker, Banque Nationale du Canada, Loto-Quebec with a focus on Alcan - Meade, JoAnn (Université McGill, 2000)

La critique littéraire au Québec en 1950: analyse de La Presse, Le Quartier latin, Le Devoir et Lectures - Deslierres, Deborah (Université McGill, 2005)
Keywords: Devoir (Le); Presse (La); Quartier latin (Le)

Accessibility: A Performance Measure for Land-Use and Transportation Planning in the Montréal Metropolitan Region - Cerdá, Assumpta (Université McGill, 2009)
Keywords: Navettage

The (Spatialized) Hub-and-Spoke Industrial District Model: An Empirical Case Study of Montreal’s Aerospace Sector - Binkovitz, Isaac (Université McGill, 2009)
Keywords: Avionnerie

Using E-Government to Strengthen Montreal's Chinese Ethnic Economy - Han, Yang (Université McGill, 2006)
Keywords: Chinois; Commerce de détail; Internet

Vivre comme frères: Native-French Alliances in the St Lawrence Valley, 1535-1667 - Cook, Peter (Université McGill, 2008)
Keywords: Autochtones; Français

A Fragile Authority: Power and the Religious Life in the Congrégation de Notre-Dame of Montreal, 1693-1796 - Gray, Colleen Allyn (Université McGill, 2004)
Keywords: Congrégation de Notre-Dame

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

Le personnage de Julie Bruneau dans la correspondance de Papineau - Arbach, Marla (Université McGill, 2001)
Keywords: Papineau, Louis-Joseph

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

Intersecting Discourses: Deaf Institutions and Communities in Montreal, 1850-1920 - Perreault, Stéphane- D (Université McGill, 2003)
Keywords: Clercs de Saint-Viateur; Communautés religieuses; Institution des sourdes-muettes; Institution des sourds-muets; Soeurs de la Providence; Sourds

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

L'éducation "idéale" dans un monde "idéal": le Dunham Ladies' College / St. Helen's School et l'élite anglicane du diocèse de Montréal (1870-1930) - Harbec, Marie-Ève (Université McGill, 2001)
Keywords: Anglicans

Organized Righteousness Against Organized Viciousness: Constructing Prostitution in Post World War I Montreal - Herland, Karen (Université McGill, 2005)
Keywords: Prostitution

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

Mobilizing Canada: the National Resources Mobilization Act, the Department of National Defence, and Compulsory Military Service in Canada - Byers, Daniel Thomas (Université McGill, 2000)
Keywords: Conscription; Guerre

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Collective Memory and Diasporic Articulations of Imagined Homes: Armenian Community Centres in Montreal - Manjikian, Lalai (Université McGill, 2005)
Keywords: Arméniens

'Justice in the Premises': Family Violence and the Law in Montreal, 1825-1850 - Pilarczyk, Ian C. (Université McGill, 2003)
Keywords: Criminalité; Droit; Enfants; Famille

Salsa and its Transnational Moves: The Commodification of Latin Dance in Montreal - Pietrobruno, Sheenagh (Université McGill, 2001)
Keywords: Danse

Making and Using Environmental Information: An Analysis of the Development and Use of Two GIS Tools for Public Environmental Engagement - Klinsky, Sonja (Université McGill, 2004)
Keywords: West Island

Transition of Asylum Seekers from Shelters to Independent Living - Balyejjusa, Moses Senkosi (Université McGill, 2009)

"To Be Sold, a Negro Wench": Slave Ads of the Montreal Gazette, 1785-1805 - Extian-Babiuk, Tamara (Université McGill, 2006)
Keywords: Esclaves; Montreal Gazette; Noirs

Your Roots Will Be Here, Away from your Home: Migration of Greek Women to Montreal 1950-1980 - Dounia, Margarita (Université McGill, 2004)
Keywords: Femmes; Grecs

Privacy in Homes of Shaamy Muslim Immigrants: A Study of Privacy Patterns in Single-Family Detached Homes and Townhouses of Middle-Class Immigrants in Montreal - Hallak, Mahmoud Essam (Université McGill, 2000)
Keywords: Musulmans; Syriens

Effect of Premigratory Exposure to Political Violence on the Social Anchorage of Refugees in Montreal - Drapeau, Aline (Université McGill, 2001)

Dietary Outcomes of a School-Based Trial to Reduce Risk Factors for Coronary Heart Disease - Esslinger, Krista (Université McGill, 2000)
Keywords: Alimentation; Diététique

Climate Change Adaptation and Mitigation through Urban Agriculture: A Montreal Case Study - Lebedeva, Julia (Université McGill, 2008)
Keywords: Climat

L'article 29 de la convention de Montréal: clef de voûte de la responsabilité du transporteur aérien international - Chassot, Laurent (Université McGill, 2009)
Keywords: Aéroport

The Feminization of Clerical Work in Early Twentieth-Century Montreal - Boyer, Laura Kate (Université McGill, 2001)
Keywords: Femmes; Travail

Examining the Overrepresentation of Black Males in the Young Offender System - Johnson, Druscilla (Université McGill, 2000)
Keywords: Délinquance; Noirs

Not a Place, but a Culture: The Cultivation of Iranian Subjectivity in Montreal - Hashemzadeh, Kianoosh (Université McGill, 2009)
Keywords: Iraniens

Intégration et transnationalisme chez les Dominicains de Montréal - Dancause, Jacques-Luc (Université McGill, 2001)
Keywords: Caribéens

Cultural Sensitivity in the Context of Ethnic Polities: A Comparison of Two Families Service Agencies - Leung, Ho Hon (Université McGill, 2001)
Keywords: Chinois; Famille; Juifs

Political Economy, Transnationalism, and Identity: Students at the Montreal Hoshuko - Yoshida, Reiko (Université McGill, 2001)
Keywords: Japonais; Nationalisme

Reconstructing Tamil Masculinities: Kavati and Viratam among Sri Lankan Men in Montréal - Gross, Victoria (Université McGill, 2008)
Keywords: Sri Lankais

Young Second Language (L2) Learner's Meaning-Making: Consciousness, Collaboration, and Creativity (3Cs) - Kim, Mi Song (Université McGill, 2008)
Keywords: Coréens; Langue

Du silence à l'affirmation: Women Making History in Point St. Charles - Kruzynski, Anna (Université McGill, 2004)
Keywords: Femmes; Pointe-Saint-Charles; Quartiers

Prendre et trouver sa place: discours hétéronormatifs et pratiques hétérosexuelles dans un cruising bar de Montréal - Lebrun, Aurélie (Université McGill, 2003)
Keywords: Alcool

The Conservation of a Gender Fantasy: Women and Top 40 Radio in Montreal - Maki, Christine (Université McGill, 2008)
Keywords: Femmes; Radio

Implementing a Sex Education, STDs and HIV/AIDS Prevention Program in a Child Welfare Setting: Implications for Service Delivery - Di Sessa, Anna Maria (Université McGill, 2000)
Keywords: Enfants

Programmes intersectoriels pour les enfants exposés à la violence conjugale: recension des écrits et pistes d'actions pour la région de Montréal - Harper, Elizabeth (Université McGill, 2003)
Keywords: Enfants; Famille

Critical Friends Groups at Lower Canada College: The Impact of Collaborative Communities on Teachers' Professional Growth and Classroom Practices - Moore, J. Brian (Université McGill, 2004)
Keywords: Enseignants; Lower Canada College

The Physical Design of Alleys: An Evaluation of Alleys in the Montreal Plateau - Wise, David (Université McGill, 2004)
Keywords: Plateau Mont-Royal; Quartiers

Making Montreal's Indoor City Accessible for People with Disabilities - Hagg, Matthew (Université McGill, 2009)
Keywords: Espace souterrain

Visual Art/Public Art and Urban Development: A Case Study of Montreal (1967-1992) - Boyce, Margaret (Université McGill, 2001)
Keywords: Centre canadien d'architecture; Jardins; Squares

Preserving Old Buildings: Adaptive Use for Residential Purposes in Montreal - Vujadinovic, Milenko (Université McGill, 2002)
Keywords: Conservation; Patrimoine

New Urbanism in Practice: An Analysis of Five Greater Montreal Area Neighbourhoods - Vannelli, Jason (Université McGill, 2009)
Keywords: Griffintown; Quartiers; Rosemont; Saint-Laurent (ville); Île-des-Soeurs

God's Mobile Mansions: Protestant Church Relocation and Extension in Montreal, 1850-1914 - Trigger, Rosalyn (Université McGill, 2004)
Keywords: Protestants; Églises

How Does what's Bred in the Bone Come Out in the Flesh? Devora Neumark's Interventions and the Concept of Flesh - Kiriloff, Vera (Université McGill, 2005)

L'histoire par l'image: commémoration picturale, pouvoir politique et stratégies visuelles au Québec (1880-1930) - Roy, Nathalie Anne (Université McGill, 2005)

Outdoor Play Areas for Children in High-Density Housing in Montreal - Aggarwal, Monica (Université McGill, 2001)
Keywords: Enfants; Parcs; Plateau Mont-Royal; Quartiers

The Stories Told: Indigenous Art Collections, Museums, and National Identities - Dickenson, Rachelle (Université McGill, 2005)
Keywords: Autochtones; Musées

Stewardship as Partnership: A Comparative Study of Positive Human-Environment Relationships in East Cree and Suburban Montreal Communities - Forrest, Margaret Anne (Université McGill, 2006)
Keywords: Banlieue; Parcs; Pointe-Claire

Crisis? What Crisis?: Anglophone Musicmaking in Montreal - Stahl, Geoff (Université McGill, 2003)
Keywords: Anglophones; Musique

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (Université McGill, 2000)
Keywords: Quartiers; Rues; Saint-Henri

Blanche Lemco van Ginkel and H.P. Daniel van Ginkel: Urban Planning - Hodges, Margaret Emily (Université McGill, 2004)

Art, identité et Expo 67. L'expression du nationalisme dans les œuvres des artistes québécois du Pavillon de La Jeunesse à l'Exposition universelle de Montréal - Hellman, Michel (Université McGill, 2005)
Keywords: Expositions; Nationalisme

La letteratura dell'emigrazione italo-canadese di Montréal - Tedeschi, Antonio (Université McGill, 2000)
Keywords: Italiens

In the Shadow of the Mountain: A Historical Re-Evaluation of the 1988 Outremont Dispute - Herman, Dana (Université McGill, 2003)
Keywords: Juifs; Outremont

Italian Identity in Montreal: Issues of Intergenerational Ethnic Retention - De Martinis, Lucio (Université McGill, 2005)
Keywords: Italiens

In Search of Communal Identity: The Role of the Black Community in Identity Formation among Nigerian Youth - Ogbuagu, Buster C. (Université McGill, 2007)
Keywords: Nigériens; Noirs

Hearing (Unheard) Voices: Aboriginal Experiences of Mental Health Policy in Montreal - Macdonald, Mary Ellen (Université McGill, 2003)
Keywords: Autochtones

Growing Up in Three Languages: Triliteracy Practices of Chinese Immigrant Children in Quebec - Curdt-Christiansen, Xiao Lan (Université McGill, 2003)
Keywords: Chinois; Langue

The Emigration of Adam Smith's Ploughman: A Case Study of the Intellectual Culture of Scots Emigrants to Lower Canada, 1760-1850 - Gibson, Sarah Katherine (Université McGill, 2007)
Keywords: Écossais

HIV Risk Behaviour and Predictors of Initiation into Prostitution among Female Street Youth in Montreal, Canada - Weber, Amy E. (Université McGill, 2001)

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith, Donald